Uptake, Translocation, and Stability of Oxytetracycline and Streptomycin in Citrus Plants - Fuad Al-Rimawi; Faraj Hijaz; Yasser Nehela; Ozgur Batuman; Nabil Killiny (MDPI AG, 2019)
Huanglongbing (HLB), or citrus greening, is the most destructive disease to the citrus industry. In Florida, it is caused by the bacterium, Candidatus Liberibacter asiaticus (CLas) and is transmitted by the Asian citrus psyllid, Diaphorina citri. Recent studies suggested that antibiotics could inhibit the growth of the CLas pathogen in planta. In the current study, we investigated the uptake and translocation of oxytetracycline and streptomycin in citrus seedlings. Oxytetracycline and streptomycin were delivered via root and stem and their level in various tissues was monitored using enzyme-linked immunosorbent assay (ELISA). Oxytetracycline and streptomycin were detected in the leaves, xylem, phloem, and root after root drench and stem delivery. High levels of antibiotics were detected in the roots after root drench, whereas high levels of antibiotics were detected in the canopy after stem delivery. The level of oxytetracycline detected in the phloem, xylem, and leaves after root drench was higher than that of streptomycin. Whereas the level of streptomycin in root was higher than that of oxytetracycline, indicating that streptomycin was bound to the xylem tissues. Oxytetracycline and streptomycin were detected in the phloem, xylem, leaves, and root tissues thirty-five days after the root incubation in 200 µg·mL−1 solution. These results demonstrated that oxytetracycline and streptomycin were relatively stable and could inhibit CLas growth for a couple of months in citrus trees. Observations reported in this study regarding the distribution and stability of oxytetracycline and streptomycin in citrus plants could be useful for designing an effective program for the control of HLB disease using antibiotics.